If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -4(y + -5) = 4 Reorder the terms: 8y + -4(-5 + y) = 4 8y + (-5 * -4 + y * -4) = 4 8y + (20 + -4y) = 4 Reorder the terms: 20 + 8y + -4y = 4 Combine like terms: 8y + -4y = 4y 20 + 4y = 4 Solving 20 + 4y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 4y = 4 + -20 Combine like terms: 20 + -20 = 0 0 + 4y = 4 + -20 4y = 4 + -20 Combine like terms: 4 + -20 = -16 4y = -16 Divide each side by '4'. y = -4 Simplifying y = -4
| 7+4y=-5 | | 4x-7=9x+11 | | 6X^2+4X-4=66 | | (2-4x)-(3-4x)+4=(-3+6x)+x | | 2[-(x-1)+4]=5+[3(2x-4)-3x] | | t+2=5 | | 8x^2+10xy-63y^2=0 | | 4x^2+16xy+7y^2=0 | | 15+(3x-2)=(15+3x)-2 | | 4.5(0.1p-0.2)+p=12.1065 | | 4008=233d+12 | | 17-5x=11-7x | | 9+8x=16+x | | x^2=9-y^2 | | 2-2x-10=6x+4 | | -7(2t+7)=-119t | | -7(2t+7)=119t | | 5(f-9)=-50 | | -10(s+5)=25 | | 12x^2-59xy+72y^2=0 | | -4(2t+7)=-52 | | 3(f-10)=-21 | | -10(s+2)=43 | | 3x^3=4x+11 | | 2(4s+10)=116 | | 5(2l+7)=135 | | 3(a-10)=3 | | 4cosx+2sinx=3 | | (q-6)*3=9 | | (q-6)*4=9 | | 6(3s+8)=156 | | 5(a-3)=65 |